Drought discourse and water crisis:: an analysis the "Ceará Water Belt" - SILVA, JOSIER FERREIRA; NOBRE, FRANCISCO WLIRIAN (Sustainability in Debate, 2016)
The main goal of this study is to analyze how the discourse about drought in the Brazilian Northeast has legitimized throughout history truths that influence the creation of public policies that do not interact with region's semiarid status. Using discourse analysis methodology we conclude that the perpetuation of "fight the drought" discourse is still used to justify the implementation of large water projects conceived to service new demands and new territories of capitalist accumulation. In the state of Ceará, which has restructured itself in order to be in line with the globalized economy, the controversial construction of the "Ceará Water Bekt" has been defended as the final solution for local water scarcity. This idea is reinforced in journalistic materials published in Ceara´s newspaper Diário do Nordeste, reinforcing the stigmatized image of the drought.